Great writing 3 : - Folse, Keith S. (Cengage Learning, 2010)
Great Writing 3: From Great Paragraphs to Great Essays takes a step-by-step approach that centers on the essential processes and organizational strategies of teaching students how to effectively transition from paragraphs to essays.